New catalytic strategies for the enantioselective synthesis of stereogenic-at-phosphorus(V) compounds - Marsh, TGF (2022)
A 2nd-generation enantioselective catalytic desymmetrisation for direct access to enantioenriched P(V) stereocentres is described. Through use of a prochiral P(V) electrophile containing two thiazolidinone leaving groups and harnessing a bifunctional iminophosphorane (BIMP) superbase catalyst, this desymmetrisation protocol delivers consistently high yields (up to 99% isolated yield) and enantiomeric excess (up to 97% ee) with a broad range of nucleophiles and P(V) electrophiles. The reaction was successfully scaled up to 3.0 mmol (1g scale), delivering product in 71% yield and 94% ee. In addition, the unique modularity of this system was demonstrated, with downstream nucleophilic displacement of the second thiazolidinone leaving group enabling stereoselective access to a broad range of chiral P(V) compounds containing P-O, P-N, P-S, and P-C linkages.